Estimation of heritability of milk yield through analysis of variance in a repeated measures design in Holsteins - Dogan, I; Özçelik, M; Dogan, N (Tubitak Scientific & Technological Research Council Turkey, 1999)
In this study, data relating to the milk yield of a Holstein herd on Bala State Farm was analysed for the period 1985-92. The aim of this study was to estimate the heritability of the milk yield using two-factor experiments with repeated measures on one factor. The heritability of the milk yield was estimated to be 0.36.
Tekrarli Ölçüm Düzenlerinde Variyans Analizi Yöntemi ile Holştaynlarda Süt Veriminin Kalitim Derecesinin Tahmini
Keywords: The analysis of variance in repeated measures design; heritability; Holstein; milk yield